Analisis Struktur Geologi Untuk Perencanaan Dan Pengembangan Project LNG Papua Barat - Citra Wahyu Ningrum; Lady Antira; Imam Salman (Pusat Riset dan Inovasi Nasional, 2023)
Eastern Indonesia is a geologically complex region. Until now, the research carried out in Eastern Indonesia and the surrounding area is still not comprehensive, so further studies and research are continuing. Research that continues to be done in Eastern Indonesia, especially in the Bird's Head region, provides various hypotheses regarding the structure and tectonics that develop in the area. Bintuni Fault Zone (Bintuni Fault Zone - SFZ) is a young structure that develops in the northern part of Papua, extending up to 1000 km from the eastern to the western Bird's Head. The purpose of this study was to determine the continuity of the direction patterns of the Bintuni Fault structure that developed in the Bintuni and surrounding areas. The method used to determine the clarity of the Bintuni Fault structure can be known from the rock outcrop data that has been passed by the fault, which is in the form of structural data. The results showed that the Bintuni Fault as a strike slip fault along its fault zone in a shear zone can form a stepover, a zone that experiences depression and ridge that occurs due to transpression and transtension forces. This identification isbased on the discovery of some evidence in the field, in the form of fault data with slicken sides found at the TKS-01.